Effectiveness of yoga for major depressive disorder: A systematic review and meta-analysis - Wu, Yufei; Yan, Danni; Yang, Jianli (Frontiers in Psychiatry, 2023)
Objective: Major depressive disorder (MDD) has a relapse rate that cannot be ignored and places a tremendous burden on the patient in the prevention and treatment process. Yoga, as a combination of physical and mental exercises, has been shown to be effective and acceptable for the adjunctive treatment of MDD. This study aims to further explore the evidence of the efficacy of yoga for patients with MDD. Methods: PubMed, Embase, and the Cochrane library databases for the period from the build to October 13, 2022, were searched by a predefined search strategy. RCTs of patients with MDD who met diagnostic criteria for Yoga treatment were included. RoB2.0 was used to evaluate the quality of the literature. Improvement in depressive symptoms was assessed by Beck depression inventory (BDI), Hamilton depression rating scale (HDRS), or other scales was used as primary outcome indicator and improvement in anxiety as assessed by Hamilton anxiety scale (HAMA), State trait anxiety inventory (STAI) scales as secondary outcome indicators. RR and Cohen's d at 95% CI were used as effect size estimates and Q and I2 were used to evaluate the size of heterogeneity with P less than 0.05 indicating statistical significance. Results: Thirty-three RCT studies, including 1024 patients in the treatment group as well as 961 patients in the control group, 74.4% of whom were women, were included in the study. Compared to the control group, the BDI-II results yielded a moderate effect of yoga on the improvement of depressive symptoms (Cohen’s d= -0.65; 95% CI: -1.01 to -0.30; P < 0.01), the HAMD results yielded a significant improvement of yoga on the severity of depressive symptoms (Cohen’s d = -0.87; 95% CI: -1.31 to -0.42; P < 0.01;), and the STAI results can be concluded that yoga had a small effect on the improvement of the level of anxiety (Cohen’s d = -0.26; 95% CI: -0.48 to -0.04; P = 0.02). No adverse events occurred in the yoga group during the treatment. Conclusion: Yoga can assist in improving depressive symptoms and anxiety in patients with MDD and has a safe and wide patient acceptance.